Distribution of maxillofacial fracture treatment using a titanium plate - Arviana, Nicky; Sjamsudin, Endang; Yuza, Abel Tasman (Padjadjaran Journal of Dentistry, 2015)
Introduction: Maxillofacial fracture is a condition of the facial bones discontinuity in the mandible, maxilla, nasal, zygoma, palate, frontal and orbital. Treatment method of maxillofacial fractures is a close reduction or open reduction by internal fixation using titanium plates. This study was aimed to describe the fixation of maxillofacial fractures using titanium plates and also, to determine the further use of titanium plates as a fixation device at the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry Universitas Padjadjaran and Hasan Sadikin Hospital. Methods: The research was a descriptive retrospective study with accidental sampling technique on the maxillofacial fracture fixation cases using titanium plates at the Department of Oral and Maxillofacial Surgery Hasan Sadikin Hospital. The samples were 135 medical records diagnosed with maxillofacial fractures. Results: The result shows that the use of titanium plates were 82.24% of the total maxillofacial fracture cases. Conclusion: There are 135 patients with a diagnosis of maxillofacial fractures treated at the Oral and Maxillofacial Surgery, Faculty of Dentistry Universitas Padjadjaran and Hasan Sadikin Hospital in 2006-2010. Most cases were treated with open reduction (108 cases) and fixed by using a titanium plate (88 cases) as well as the combination of a titanium plate with a wire (12 cases).